Evaluasi Program Pendidikan dan Pelatihan Kewirausahaan - Liliana, Chyntia; Kurnaningsih, Yari Dwi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to evaluate the entrepreneurship education and training activities program that uses the Kirkpatrick evaluation model. Data collection using questionnaires, observations, interviews and document studies. Data were analyzed in quantitative descriptive qualitative. Qualitative data analysis was carried out through three stages: The results showed that at the reaction level, 85.20% of participants were satisfied with the organization of entrepreneurship education and training. At the learning level, knowledge aspects did not experience a significant increase. In the aspect of attitudes and skills of training participants considered very good. At the behavioral level, 6 people have done business planning and have successfully run their businesses, 5 people have planned businesses, but have not yet started their businesses, while 14 people have not had business plans.Abstrak: Penelitian ini bertujuan untuk mengevaluasi program kegiatan pendidikan dan pelatihan kewirausahaan yang menggunakan model evaluasi Kirkpatrick. Pengumpulan data menggunakan angket, observasi, wawancara, dan studi dokumen. Data dianalisis secara deskriptif kualitatif kuantitatif. Analisis data kualitatif dilakukan melalui tiga tahap, yaitu hasil penelitian menunjukkan bahwa pada level reaction, sebesar 85,20% peserta puas terhadap penyelenggaraan pendidikan dan pelatihan kewirausahaan. Pada level learning, untuk aspek pengetahun tidak mengalami peningkatan yang signifikan. Pada aspek sikap dan keterampilan peserta pelatihan dinilai sangat baik. Pada level behavior, enam orang telah melakukan perencanaan usaha dan telah berhasil menjalankan usahanya, lima orang sudah merencanakan usaha, namun belum memulai usahanya, sedangkan 14 orang belum memiliki perencanaan usaha.